Pengaruh Perawatan Luka Modern Dressing Tribee Salep Terhadap Mencegah Infeksi pada Penyembuhan Luka Post Laparatomi Eksplorasi Apendiktomi Dirs Yarsi Cempaka Putih - Kenanga Fatmariza Mahestia (Vitamin : Jurnal ilmu Kesehatan Umum, 2026)
Appendicitis is inflammation and obstruction of the vermiform appendix and is the most common cause of acute abdomen. A surgical wound is said to be infected if the wound discharges pus or pus and is likely infected if it shows signs of inflammation or discharges serous discharge. The purpose of this study was to determine the effect of modern wound care dressing tribee ointment on preventing infection in wound healing after laparotomy exploration appendectomy at Yarsi Cempaka Putih Hospital. The method in this study was pre-experiment one group pre-test and post-test. The population and sample were 18 respondents. The results of the study showed the effect of modern wound care dressing tribee ointment in preventing infection in wound healing in patients after laparotomy exploration appendectomy at Yarsi Cempaka Putih Hospital with a p value of 0.000 <0.05. The conclusion is that there is an effect of modern wound care dressing tribee ointment in preventing infection in wound healing in patients after laparotomy exploration appendectomy.